2005
DOI: 10.1074/jbc.m407060200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 Has Opposing Effects on the Proliferation and Migration of Endothelial Cells

Abstract: Pathological conditions such as hypertension and hyperglycemia as well as abrasions following balloon angioplasty all lead to endothelial dysfunction that impacts disease morbidity. These conditions are associated with the elaboration of a variety of cytokines and increases in p38 activity in endothelial cells. However, the relationship between enhanced p38 activity and endothelial cell function remains poorly understood. To investigate the effect of enhanced p38 MAPK activity on endothelial cell function, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 61 publications
11
86
0
1
Order By: Relevance
“…Previously studies have reported that p38MAPK induces phosphorylation of the heat shock protein-27 (HSP27), a molecular chaperone, and it positively regulates VEGF-induced actin reorganization and migration (7,27). Therefore, we examined the effect of PI on VEGF-A-induced phosphorylation of p38MAPK.…”
Section: Discussionmentioning
confidence: 97%
“…Previously studies have reported that p38MAPK induces phosphorylation of the heat shock protein-27 (HSP27), a molecular chaperone, and it positively regulates VEGF-induced actin reorganization and migration (7,27). Therefore, we examined the effect of PI on VEGF-A-induced phosphorylation of p38MAPK.…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of p38 MAPK augments VEGFinduced angiogenesis in the chicken chorioallantoic membrane (CAM) assay (Issbrucker et al, 2003;, without an accompanying increase in vascular permeability (Issbrucker et al, 2003). Moreover, p38 MAPK induces phosphorylation of heat-shock protein-27 (HSP27), a molecular chaperone that positively regulates VEGFinduced actin reorganization and migration (McMullen et al, 2005;Rousseau et al, 1997).…”
Section: Vegf Signalingmentioning
confidence: 99%
“…For example, microinjection of a neutralizing anti-p38 antibody into NIH3T3 mouse fibroblast during the G 1 phase resulted in cell cycle arrest at the G 1 /S boundary, 53 but p38 has a negative impact on proliferation in endothelial cells. 54 Several mechanisms have been suggested, including phosphorylation of p53 and p21 WAF1/CIP1 , stabilization of the transcriptional repressor HBP1, and reduction in cyclin D stability and transcription. [55][56][57][58][59][60] Among the primary substrates for p38 is the transcription factor ATF2, 61 which is phosphorylated at residues 69 and 71 by p38 in response to wide range of stimuli, resulting in its transcriptional activation of cell cycle regulatory genes such as cyclin A and cyclin D1.…”
Section: P38 Kinase In Cell Cycle Regulationmentioning
confidence: 99%